Consumer Trust and Consumptive Behavior in Online Shopping among Students - Anggun, Anggun Citra Mahgfiroh; Hardiansyah, Eko (Jurnal Psikologi Teori dan Terapan, 2024)
Background: In an online learning environment, consumer trust is crucial for helping consumers understand perceptions of risk and repercussion. Objective: to determine the relationship between consumer trust and consumptive behavior of students. Method: This research uses a correlational quantitative approach that aims to determine the relationship between two or more variables. The sampling method in this study used a random sampling approach, with a total sample size of around 241 students consisting of 34 men and 207 women. Results: According to the findings, the majority of students had moderate levels of consumer trust (59.8%) and consumptive behavior (80.9%). A coefficient value of 0.426 indicates a reasonably significant correlation between the two variables in the data analysis test. There is 0.000 p-value between student’s consumer trust and consumptive behavior, with an alpha of 5%, we can conclude that the correlation between the two variables is significant since 0.000>0.05, Conclusion: According to the findings, the likelihood of engaging in consumptive behavior when shopping online increases with consumer trust.